Between probability and certainty what justifies belief - Smith, Martin (Oxford University Press, 2016)
Martin Smith explores the question of what it takes for a belief to be justified or rational. He argues that in order to have justification for believing a proposition, one's evidence must normically support it-roughly, one's evidence must make the falsity of that proposition abnormal in the sense of calling for special, independent explanation.